Pengaruh Kreativitas Dan Passion Berwirausaha Terhadap Intensi Berwirausaha (Studi Kasus Pada Mahasiswa Manajemen Bisnis Syariah STAIN Mandailing Natal) - Mirliza Gusma Widya; Vebri Sugiharto; Muhammad Ardiansyah (CV. ITTC INDONESIA, 2025)
One of the causes of rising unemployment in Indonesia is the lack of job oppourtunities, Which, if not addressed, will pose a social threat to society. Efforts that can be made include increasing the number of entrepreneurs, one of which is by fostering entrepreneurial intent among university students. The purpose of this study is to determine the partial and simultaneous effects of creativity and passion for entrepreneurship on entrepreneurial intention among student of sharia business management at STAIN Mandailing Natal. The study was conducted in the sharia business management program with all sharia business management students as the data source. The data analysis method used was quantitative, consisting of observation results and questionnaire data answered by respondents. The analysis results show that 62% of creativity and entrepreneurial passion influence entrepreneurial intention. The hypothesis test results for creativity show at-value of 5.807 and a t-table value of 1.974, while the hypothesis test results for entrepreneurial passion show a t-value of 8.668 and a t-table value of 1.974 (calculated t > table t) so H0 is rejected and Ha is accepted. Therefore, it can be concluded that there is an influence between creativity and entrepreneurial passion on entrepreneurial intention among sharia business management student at STAIN Mandailing Natal.